Hormones, heredity, and race : spectacular failure in interwar Vienna - Logan, Cheryl A. (Studies in modern science, technology, and the environment., 2013)
In the early twentieth century, arguments between "nature" and "nurture" pitted a rigid genetic determinism against the idea that genes were flexible and open to environmental change. This book tells the story of three Viennese biologists who sought to show how the environment could shape heredity through the impact of hormones and explores the dynamic of failure in science through both scientific and social lenses.